Juvenile Dermatomyositis in Turkish Children - Sebahat TÜLPAR; M. Hakan POYRAZOĞLU; Zübeyde GÜNDÜZ; Ruhan DÜŞÜNSEL; Funda BAŞTUĞ (Archives of Rheumatology, 2011)
Objectives: This study aims to determine the clinical features of juvenile dermatomyositis (JDM) in Turkish children. Patients and methods: The clinical records of nine children with JDM who were followed up in the Department of Pediatric Nephrology and Rheumatology of Erciyes University Faculty of Medicine between January 1992 and December 2008 were reviewed retrospectively. Results: The female to male ratio was 2:1. The median age at onset of the disease was 8.8 years (range 6.5-14 years), the median duration of symptoms before diagnosis was two months (range 10 days-72 months), and the mean time of follow-up was 49.5 months (range 2-96 months). The main presenting complaints were arthritis/arthralgia, myalgia, an impaired ability to walk, and skin rashes. Eight patients received oral steroids as the initial therapy. Additionally, two patients received intravenous methylprednisolone, and five received non-steroidal antiinflammatory drugs during the follow-up. Three patients received methotrexate, and one received cyclosporine A. The median time to treatment response was 60 days (range 10-70 days). Pathological proteinuria was found in two patients. Subcutaneous calcinosis developed in one patient. Skin and soft-tissue infections occurred in two patients. Other complications seen during the follow-up were malnutrition, obesity, depressive mood, ototoxicity, muscle weakness, osteoporosis, and contractures. Conclusion: Although juvenile dermatomyositis is a rare disease in childhood, it may have severe complications.